The Balkans – geopolitics of a mirror broken into pieces - Bertalan, Péter; Nagy, András (Acta Scientiarum Socialium, 2015)
The aim of the study is to show a new geopolitical approach to the understanding of international processes. The authors come up with the idea of connecting geographical elements with international relations and the moves of great powers and smaller states. The new approach of matching geographical fault lines with the region of Central-Eastern Europe, a region between the Baltic and the Black Sea provides us with a deeper view on international events and networks. Connecting the two fields of research, geography and international diplomacy, the authors describe the short 20th century and the beginning of the 21st century as the period of earthquakes and volcanic eruptions along the fault lines, concentrating on the history of the Balkan region, providing us with a better understanding of the international system and the situation of smaller states among the great powers.
Keywords: Geopolitical fault lines; 20th century political history; First and Second World Wars